Conservation in Brazil needs to include non‐forest ecosystems - Overbeck, Gerhard E; Vélez‐Martin, Eduardo; Scarano, Fabio R; Lewinsohn, Thomas M; Fonseca, Carlos R; Meyer, Sebastian T; Müller, Sandra C; Ceotto, Paula; Dadalt, Letícia; Durigan, Giselda; Ganade, Gislene; Gossner, Martin M; et al. (Diversity & distributions, 2015)
In the past decades, Brazil made important progress in the conservation of forest ecosystems. Non‐forest ecosystems (NFE), in contrast, have been neglected, even though they cover large parts of the country and have biodiversity levels comparable to forests. To avoid losing much of its biodiversity and ecosystem services, conservation and sustainable land use policies in Brazil need to be extended to NFE. A strategy for conservation of Brazil's NFE should encompass the following elements: (1) creation of new large protected areas in NFE; (2) enforcement of legal restrictions of land use; (3) extension of subsidy programs and governance commitments to NFE; (4) improvement of ecosystem management and sustainable use in NFE; and (5) improvement of monitoring of land use change in NFE. If Brazil managed to extend its conservation successes to NFE, it not only would contribute significantly to conservation of its biodiversity, but also could take the lead in conservation of NFE world‐wide.